Avaliação da insolação em poços termométricos no cômputo da vazão na condição de referência - Capistrano, Igor Martins Pimentel (2023)
The flare gas flow measurement shall be reported in the standard measurement condition (reference condition). Obtaining the flow in the standard measurement condition depends on the temperature of the fluid flow, which is obtained by a temperature sensor and with the aid of a thermowell inserted in the flow. The objective of this work is to evaluate the effect of insolation in thermowells, analyze the temperature difference measured by the sensor and the actual temperature of the fluid due to the incidence of solar radiation in the wells and verify this difference in the conversion of the flow to the reference condition. The most relevant and current studies on the subject are presented, in addition to a review of the standards related to the thermowell. A fin model for the thermowell is proposed in order to obtain the temperature profile from a mathematical model; numerical simulations are presented under different operating conditions; the results of experiments performed with a thermowell available in the laboratory are presented and, finally, the comparison between the three approaches. The results indicate that the experiments were carried out at speeds similar to the operational condition in flare gas installations, the temperature profiles obtained from the numerical simulations showed maximum differences of 2% in relation to the experimental data, the fin effect suffered by the thermowell can change by 0.5% the flow measurement in the reference condition and when considering that the uncertainty of the flare gas flow can reach 5%, according to the Brazilian legislation, then this effect corresponds to 10%, approximately, of the uncertainty allowed by legislation.